2012
DOI: 10.1108/14757701211279196
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cash holdings and ownership concentration on firm valuation

Abstract: PurposeThe purpose of this paper is to investigate the impact of firms' cash holdings and ownership concentration on the firms' valuation using an unbalanced panel dataset of non‐financial listed firms in Australia.Design/methodology/approachThe author used a generalized method of moments approach suitable for unbalanced panel dataset to examine the impact of firms' cash holdings and ownership concentration on firms' q‐ratios after controlling for the impact of financing, dividend and investment decisions, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 64 publications
0
16
0
2
Order By: Relevance
“…García-Meca and Sánchez-Ballesta (2011) have reported that ownership concentration appears to influence firm value favourably, but at high levels a detrimental effect causes market valuation to be negatively affected by high levels of large shareholder ownership. Ameer (2012) found a positive relationship between cash holdings and q-ratio of Australian firms. The ownership structure moderates the effect of cash holdings on q-ratio in asymmetric fashion, i.e., for widely held firms, there is a positive relationship between cash holdings and q-ratio; while for closely held firms, there is significant negative relationship between cash holdings and q-ratio.…”
Section: Ownership Structurementioning
confidence: 97%
“…García-Meca and Sánchez-Ballesta (2011) have reported that ownership concentration appears to influence firm value favourably, but at high levels a detrimental effect causes market valuation to be negatively affected by high levels of large shareholder ownership. Ameer (2012) found a positive relationship between cash holdings and q-ratio of Australian firms. The ownership structure moderates the effect of cash holdings on q-ratio in asymmetric fashion, i.e., for widely held firms, there is a positive relationship between cash holdings and q-ratio; while for closely held firms, there is significant negative relationship between cash holdings and q-ratio.…”
Section: Ownership Structurementioning
confidence: 97%
“…Untuk mencapai firm value itu sendiri, diperlukan beragam fungsi dan kebijakan dalam menunjang kegiatan operasional dan investasi yang ada. Ameer (2012) menyatakan bahwa alokasi sebuah perusahaan dalam mengelola asetnya merupakan faktor fundamental dalam meningkatkan pertumbuhan perusahaan di masa depan yang akan secara searah mempengaruhi mengoptimalkan kesejahteraan pemegang saham. Dari sudut pandang investor sendiri, tinggi-rendahnya firm value akan tercermin melalui harga pasar saham sebuah perusahaan tersebut (Walker, 2000).…”
Section: Pendahuluanunclassified
“…() show that even though higher cash holdings are associated with lower cash values on average, Australian firms facing higher uncertainty of greater financial constraint benefit from holding cash that otherwise appears excessive. Ameer () show that Australian firms with higher ownership concentration, and therefore potential control problems, have a negative relation between q and cash holdings while lower ownership concentration firms have a positive relation. I do not directly address agency problems and the value of cash, but note that the model estimates suggest different measures of financial constraint more closely relate to supply of financing effects while others relate to demand for financing effects.…”
Section: Introductionmentioning
confidence: 99%